Islamic Bank and Corporate Social Responsibility - Lina Marlina (Journal of Islamic Economics Literatures, 2020)
Research purposes– Corporate Social Responsibility (CSR) is one of the rapidly growing issues in today's business and has become a new norm in the social system, including for Islamic financial institutions, one of which is the Islamic Bank. With the shift in the world paradigm related to the responsibility of a business, CSR has become a substantial issue for academics and practitioners in the last two decades and has become an intense and interesting discussion to date. This study aims to determine the development of research trends in CSR of Islamic Banks around the world published by leading journals related to this theme. Research methodology – The author uses qualitative-quantitative research with a bibliometric analysis approach. The data used consists of indexed research publications, then processed and analyzed using the Vos Viewer application to know the bibliometric map of the development of CSR of Islamic Bank research in the world. Findings – The results of this study are to identify authors, institutions, countries, and keywords related to CSR of Islamic Bank. Limitation – The data used in this study are limited to the Scopus database and English reviews. Originality/Value – To the author's knowledge, this study is the first to discuss literature related to CSR of Islamic Banks in the world from a bibliometric aspect. The results of this study are expected to help researchers and practitioners to further explore research related to this theme.